2001
DOI: 10.1364/ao.40.000327
|View full text |Cite
|
Sign up to set email alerts
|

Compact adaptive optical system based on blind optimization and a micromachined membrane deformable mirror

Abstract: We describe and demonstrate an adaptive optical system based on the combination of a micromachined membrane deformable mirror and the stochastic parallel gradient descent control algorithm. This compact and relatively inexpensive adaptive optical system is used to maximize the coupling of a distorted laser beam into a single-mode optical fiber. The coupling efficiency is improved by 12 dB, and the coupling efficiency after correction is 64% of the diffraction-limited coupling efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…AO is effective for optimizing spatial modes for coupling applications [11,12] and nonlinear optics [13]; however, AO can be difficult in the low-intensity limit, where wavefront measurements are unreliable and photon count fluctuations can thwart traditional gradient methods of system optimization. In this regime, AO must be performed entirely at the single-photon level [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…AO is effective for optimizing spatial modes for coupling applications [11,12] and nonlinear optics [13]; however, AO can be difficult in the low-intensity limit, where wavefront measurements are unreliable and photon count fluctuations can thwart traditional gradient methods of system optimization. In this regime, AO must be performed entirely at the single-photon level [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Also it is worth considering to use reduced precision data representation: working in single precision, rather than double, gives a substantial performance improvement. 10 To the best of the authors' knowledge, only a small number of papers [11][12][13] have considered the use of constrained MPC/RHC to control deformable mirrors in adaptive optics. MPC was used 11 to control a Thermal Deformable Mirror in order to correct static aberrations in a light beam.…”
Section: Introductionmentioning
confidence: 99%
“…An AO system based on the combination of a membrane DM and a stochastic parallel gradient descent control was presented in. 13 The purpose of this paper is to analyse the feasibility of RHC with QP for use in astronomical adaptive optics. The dynamics of the DM are considered to consist of first-order transfer functions.…”
Section: Introductionmentioning
confidence: 99%
“…Plett et al reported recently fiber-coupling optimization by means of the SPGD algorithm using a comparable slow system with a personal computer as controller and a 37-control-channels membrane mirror. 9 No comparison of the direct optimization of the coupling efficiency with conventional adaptive optics was performed. Since model-free optimization allows for direct CE maximization as well as modeling of phase conjugation, we are able to perform a comparison of both approaches with one system.…”
Section: Introductionmentioning
confidence: 99%